Dynamics design of mechanism of crane trolley movement - Demokritov, Vladimir; Oleshkevich, Aleksandr (Transport, 2006)
A crane trolley with a hanging oscillating load was considered. Normal and tangential acceleration of the load and difference between the weight of the load and the strain of the rope are taken into account. Three differential dynamic equations were made. After the solution of the system one nonlinear equation was got; the solution of it was found. Frequency of own vibrations, amplitude and phase were defined taking primary conditions into consideration. The condition of resonance prevention was revealed.First Published Online: 27 Oct 2010